Subordonarea marcată prin conjuncții în producțiile scrise ale studenților străini. Probleme în limba română ca limbă străină (Romanian Studies Today, 2024)
This paper aims to illustrate the contexts of conjunctive subordination and to highlight the difficulties existing in texts written in Romanian as a foreign language by non-native students enrolled in the Preparatory Year (Centre for Romanian Studies, Faculty of Letters, University of Bucharest) in the period 2019–2023, at their examination sessions. The description is based on a corpus analysis. The most striking errors are: mistakes in writing conjunctive connectors (the presence or absence of diacritics), lexical and syntactic "innovations" resulting from the overlap of several conjunctions or conjunctive groups, the absence of the conjunctive connector and the failure to express of the main verb in subordinate clauses.
Keywords: Romanian as a foreign language; subordination; subordinate clauses; conjunctions; errors